METODE PENAFSIRAN AL-QURAN: Pengenalan Dasar Penafsiran al-Qur`an - Moh Abdul Kholiq Hasan (UIN Raden Mas Said Surakarta, 2015)
As Muslim we have an obligatory to have good enoughunderstanding about the Holy Qur’an. As one ways for Muslims to getgood enough understanding and practing the essential message ofQur’an, some of the Islamic scholar published some books ofQur’anic interpretation (Tafsir). Even actually all of Muslim hasgiven good enough freedom to utilize their mind to interprete the HolyQur’an, but there were some limitations from the mind. Therefore, allof muslims are reminding to be careful to interpret the Qur’anicverses, through understanding which part of the verses which ispermitted to be interpreted and which is prohibited.Key-words: Pemahaman, Interpretasi, dan pengamalanPendahuluan